PENGGUNAAN SENJATA KIMIA OLEH SURIAH DIKAITKAN DENGAN KONVENSI INTERNASIONAL - Shenny Shenny; Lutfiyana Dewi Wahyuni; Sarah Fatwa; Syafina Ramadhanti Triana; Rivan Mandala Putra; Herli Antoni (SUPREMASI HUKUM, 2023)
This research uses a doctrinal approach based on international agreements and international conventions that aim to provide an understanding of the civil war in Syria that is linked to international conventions. The UN Security Council uses regulations to punish those who use chlorine, one of which is in the civil war, because it is related to article VII of the UN Charter. The provisions governing civil war are set forth in article 3 Kof the 1949 Jenewa convention. The Geneva Conventions and additional protocols are aimed at protecting the enemy. Syria must take responsibility for a civil war in which the United Nations as an international organization plays a role in ensuring world peace, the ICRC carries out protection and humanitarian assistance, and the international court plays a role in prosecuting war crimes and crimes against humanity. In relation to article 146 of the IV Geneva Convention which means that everyone who has been proven to have committed an offense categorized as a gross human rights violation must be tried using the national re of his country to ensure legal certainty and provide justice to the victims affected. Keywords: War, Chemical Weapons, Syria, Convention